Reproductive Biology of Acacia Mangium Willd. and Acacia Auriculiformis A. Cunn. Ex. Benth - Ibrahim, Zakaria (1991)

(untitled)
A. mangium is the most widely planted plantation species in Malaysia for general utility timber and pulp and paper. The occurrence of natural hybrids between A. mangium and A. auriculiformis has created general interest in using hybrids in the plantation programme. This study looks into the reproductive biology of A. mangium and A. auriculiformis and compares the performance of hybrid progenies and progenies of their parental species. Morphologically, the inflorescences and flowers of A. mangium and A. auriculiformis are similar. The in florescence of both species consists of numerous flowers borne on a loose spike. The flowers are small and brightly coloured. The main difference between the flowers of the two species is the colour, creamy white in A. mangium and bright yellow in A. auriculiformis. Andromonoecy is also observed in both species.